Synthesis of the JHPS International Symposium on Tritiated Water. Issue 1 (July 2021) - Yoshida, H.
As the decommissioning of Fukushima Daiichi nuclear power plant (NPP) progresses, the issue of how to deal with tritiated water has been attracting attention, both domestically and internationally. This article summarises the live discussion at the International Symposium on Tritiated Water, which was held by the Japan Health Physics Society (JHPS) in June 2020. Two issues – the scientific safety of tritiated water and social consensus building – were covered in the live discussion. The importance of further disclosure and dissemination of information based on steady monitoring was highlighted. It was also pointed out that scientific knowledge and scientific research data are merely the bottom line to achieve social consensus. Through the discussions, it was recognised that the role of JHPS is not only to look at the technical issues of safety, but also to look at social issues from the point of view of radiation protection, and to support the solution of these issues.